Evaluation of implicit associations between back posture and safety of bending and lifting in people without pain - Caneiro, J.; O'Sullivan, Peter; Lipp, Ottmar; Mitchinson, L.; Oeveraas, N.; Bhalvani, P.; Abrugiato, R.; Thorkildsen, S.; Smith, Anne (Walter de Gruyter GmbH, 2018)
Despite lack of support from recent in vivo studies, bending and lifting (especially with a round-back posture) are perceived as dangerous to the back. In light of this view, it has been proposed that pain-free people may hold a common implicit belief that is congruent with the idea that bending and lifting with a round-back represents danger to a person's back, however this has not been evaluated. The aims of this study were: (1) to evaluate implicit associations between back posture and safety related to bending and lifting in pain-free people; (2) to explore correlations between the implicit measure and explicit measures of back beliefs, fear of movement and safety of bending; (3) to investigate self-reported qualitative appraisal of safe lifting. Exploratory cross-sectional study including 67 pain-free participants (no pain, or average pain =3/10 for less than one week over the previous 12 months) (52% male), who completed an online survey containing demographic data and self-reported measures of: fear of movement (Tampa Scale for Kinesiophobia for General population - TSK-G), back beliefs (Back Pain Attitudes Questionnaire BackPAQ), and bending beliefs (Bending Safety Belief - BSB - a pictorial scale with images of a person bending/lifting with round and straight back postures). Implicit associations between back posture and safety related to bending and lifting were evaluated with the Implicit Association Test (IAT). A qualitative assessment of descriptions of safe lifting was performed. An implicit association between "danger" and "round-back" bending/lifting was evident in all participants (IATD-score=0.65 (SD=0.45; 95% CI [0.54, 0.76]). Participants' profile indicated high fear of movement, unhelpful back beliefs, and perceived danger to round-back bending and lifting (BSBThermometer: 5.2 (SD=3.8; 95% CI [4.26, 6.13] range -10 to 10; t(67)=11.09, p<0.001). There was a moderate correlation between IAT and BSBThermometer(r=0.38, 95% CI [0.16, 0.62]). There were weaker and non-statistically significant correlations between IAT and TSK-G (r=0.28, 95% CI [-0.02, 0.47]), and between IAT and BackPAQDanger(r=0.21, 95% CI [-0.03, 0.45]). Qualitative assessment of safe lifting descriptions indicated that keeping a "straight back" and "squatting" when lifting were the most common themes. Pain-free people displayed an implicit bias towards bending and lifting with a "round-back" as dangerous. Our findings support the idea that pain-free people may have a pre-existing belief about lifting, that the back is in danger when rounded. Research to evaluate the relationship between this implicit bias and lifting behaviour is indicated. The findings of this study may have implications for ergonomic guidelines and public health information related to bending and lifting back postures. Additionally, clinicians may need to be aware of this common belief, as this may be reflected in how a person responds when they experience pain.